Nouvelles approches de la ville dans la littérature française contemporaine : Thomas Clerc et Philippe Vasset - Lis, Jerzy (Wydawnictwo Naukowe UAM, 2012)
On the basis of two indecidable texts (Thomas Clerc, “Paris, musée du XXIe siècle. Le dixième arrondissement”, Gallimard 2007 and Philippe Vasset, “Un livre blanc”, Fayard 2007), we will reflect on new approaches to the city in contemporary French litterature. Clerc and Vasset, in their respective texts, suggest considering litterature as a series of practices connected with the exploration of the city (Clerc) and of the urban area (Vasset) according to the idea of an arbitrary itinerary. The image of the city whose space, subject to a permanent process of museifi cation, is constantly considered to be a work of art (Clerc) contrasts with a project of viewing the deserted areas of the city and of its surroundings as an infinite collection of “artistic installations” created in daily life (Vasset). Clerc’s and Vasset’s artistic mentality leads them to the fascination with “works of involuntary art”, both concrete signs and tangible proof of the transitional period which they try to describe systematically, following, at the same time, the principles of an axonometric city map.
New approaches to the city in contemporary French literature: Thomas Clerc and Philippe Vasset
Keywords: contemporary French literature; urban novel; city; urban area; axonometric city map